2020
DOI: 10.1177/2150132720932722
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting the #flushot: Beliefs, Barriers, and Threats During Different Periods of the 2018 to 2019 Flu Season

Abstract: Influenza epidemics happen every year, with more than 8 million severe cases in 2017. The most effective way to prevent seasonal influenza is vaccination. In recent years, misinformation regarding vaccines abounds on social media, but the flu vaccine is relatively understudied in this area, and the current study is the first 1 to explore the content and nature of influenza information that is shared on Twitter, comparing tweets published in the early flu season with those posted in peak flu season. Using a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The HBM is framed on a number of key health beliefs, such as perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy that persuade individuals to make healthy behavior changes. The HBM has been used in previous studies to characterize response to health threats such as the swine flu, tuberculosis, and others [ 41 , 42 , 43 , 44 ]. Based on the framework, smokers who perceive themselves susceptible to a threat are more likely to engage in reduction or quitting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The HBM is framed on a number of key health beliefs, such as perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy that persuade individuals to make healthy behavior changes. The HBM has been used in previous studies to characterize response to health threats such as the swine flu, tuberculosis, and others [ 41 , 42 , 43 , 44 ]. Based on the framework, smokers who perceive themselves susceptible to a threat are more likely to engage in reduction or quitting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to vaccine information sources [6], factors include the convenience of vaccination [7,8], vaccine shortages [9], and other vaccine service factors. Sociocultural structure [10], media misinformation [11,12], the humor of vaccine information [13], and social and spatial aggregation of families [14] were also associated with vaccine hesitation in previous studies.…”
Section: Literature Reviewmentioning
confidence: 73%
“…On the contrary, 8 (11%) studies found a negative public reaction to the health information available online. It is essential to understand the motivators of certain attitudes and behaviors on SMPs (Kang et al, 2017; Massey et al, 2018) and which ideologies predominate to encourage health authorities (Guidry et al, 2020) to adopt effective communication strategies (Picanço et al, 2018; Sommariva et al, 2018). Finally, the need of technology to analyze information quality was mentioned in the conclusions of 7 (10%) of the studies (Bode and Vraga, 2018; Lara-Navarra et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studying the credibility of health information on SMPs was suggested in 15 (21%) studies (Pennycook et al, 2020). Furthermore, 12 (17%) studies recommended exploring ideologies and strategies that support anti-vaccination (Blankenship et al, 2018; Guidry et al, 2020; Liao et al, 2020). Studies of the origin, diffusion, and reception of information on SMPs were also proposed in 12 (17%) studies (Niknam et al, 2021; Surian et al, 2016).…”
Section: Resultsmentioning
confidence: 99%